Spinderella - Donaldson, Julia; Pichon, Liz (New York, 2005)
When Spinderella and her seven spider siblings want to play soccer, she, along with her Hairy Godmother, must convince the others that numbers are important. Includes facts and activities relating to numbers and soccer.
Keywords: Fiction; Soccer; Fiction; Counting; Fiction; Numbers, Natural; Spiders; Fiction